Application of earthquake‐induced collapse analysis in design optimization of a supertall building. (3rd June 2016) - Lu, Xiao; Lu, Xinzheng; Guan, Hong; Xie, Linlin
Summary: In recent years, a combination of rapid construction of supertall buildings and frequent occurrence of strong earthquakes worldwide demands a rational seismic design method for structures of this kind. Although earthquake‐induced collapse analysis is one of the most efficient methods to quantify the collapse resistance of buildings, little research has been reported on using the collapse analysis to evaluate the seismic safety of supertall buildings during the design stage. To optimize the design taking into account earthquake‐induced collapses, a real‐world supertall building with a height greater than 500 m is investigated in this work. Throughout its design procedure, earthquake‐induced collapse analyses are performed to optimize the design at three different levels (i.e. the structural system level, design parameter level and component level). At the structural system level, the influence of different lateral force‐resisting systems on the collapse resistance is discussed; at the design parameter level, the influence of minimum base shear force is discussed; and at the component level, the influence of high‐performance shear wall on the collapse resistance is studied. Based on these discussions, the optimal design scheme of the building is established to improve the seismic safety while maintaining the cost of construction. Given more and more supertall buildings will be constructed with new structural system and components, this work will provide important references for the seismic design of supertall buildings and the corresponding collapse resistance research in the future. Copyright © 2016 John Wiley & Sons, Ltd.